Determination of Stability Constants of Some Transition Metal Complexes of 2-Hydroxybenzylidine-4-Toluidine - Raut, Ameya; Desai, Pulkeshi; Mangaonkar, Kiran (Asian Journal of Chemistry, 2010)
Proton dissociation constants of the ligand 2-hydroxybeozylidine-4- toluidine and the stability constants of its complexes with Co(ll), Ni(II), Cu(II), Zn(II) and Cd(II) have been determined potentiometrically at 30 ± 0.1°C and at ionic strength 0.1 M in 75:25 (v/v) dioxane-water medium. The values log K1 and log K2 have been determined. The stabilities of the chelates follow the order Cu> Zn > Co > Cd > Ni.